A formação continuada de professores de escolas públicas no/do campo: relações entre pesquisa-ação e um instrumental teórico-metodológico específico na modalidade da educação do campo - Schiochet, Fernanda Cristina (2023)
This Master's Thesis is linked to the Post-Graduate Program in Education - Master's Degree, Campus Francisco Beltrão/PR, of the Western Paraná State university Unioeste, area of concentration in Education, Research Line: Culture, Educational Processes and Teacher Formation and is entitled “The Continued Formation of Teachers of Public Schools in/from the Field: Relationships between Action Research and a Specific Theoretical-Methodological Instrumental in the Field Education Modality.” The problem poses the question of understanding the specificity of continued formation of teachers of public schools in/from the field from the perspective of the National Movement of Field Education, in the Modality of Basic Field Education. It is justified, by the existence of legislation that deals with this specificity, however the teachers are distanced from the organization of these schools and these territories, the governing bodies, in turn, are little engaged in this perspective. The research was carried out at the State Field School Castelo Branco - Primary and Secondary School, in the county of Coronel Vivida/PR. There was an ongoing reference in public schools in/from the field that develop a TheoreticalMethodological Instrumental in Modality, through an extension project of the Unioeste, campus Francisco Beltrão/PR. The methodology took place with the qualitative approach, with a fieldwork added with records collected with the participants, through individual Field Journals and in the collective of the Research Circles. Action research was used for its pedagogical and research potential, complemented with bibliographic and documentary research procedures. It was walked through categories such as Rural Education, Field Education, Public Schools in/from the field, Continued Formation of Teachers, Action Research, Pedagogical Practice and Theoretical-Methodological Instrumental. The analyzes showed that the process of continued formation of teachers in the specificity of Field Education, in public schools in/from the field, constitutes a movement "from the inside out" of the school, in thedialogue between theory and practice, which allows experimenting, reflecting and appropriating, so that teachers apprehend the specific relations of Field Education through the practice of the public school, in the space of the territory and through teaching, strengthening themselves as the school and as professionals. In this sense, the importance of action research is confirmed, since it allows teachers a continuous formation with meaning for a new type of public field school, through a formative process that reaches pedagogical practices, reality and its subjects.